Future scenarios for fast-moving consumer goods in a circular economy. (March 2019) - Kuzmina, Ksenija; Prendeville, Sharon; Walker, Dale; Charnley, Fiona
Highlights: Scenario planning is used to engage experts and users in envisioning the future of FMCG within a circular economy context. Five future scenarios to inform a vision for the future of the FMCG industry in circular economy are presented. A new perspective is presented on how value is created for circular economy and the role of the consumer and IT within it. Insights from the FMCG industry bridges a gap within the literature between the circular economy and consumer studies. Abstract: The aim of the study is to envision, through an inductive scenario planning methodology, future scenarios of the fast-moving consumer goods (FMCG) industry in the context of a circular economy (CE). The study uses an exploratory scenario planning, an inductive approach to engage FMCG industry organisations, CE experts, end-users, and academic stakeholders in exploring the future of FMCG within a CE context. Five future scenarios that can inform a vision for the future of the FMCG industry were developed: (1) Rinse and Reuse, (2) The Cycling of Pure Materials, (3) The Rise of the Circular Retailer, (4) A World Without Supermarkets and (5) Connected Living. The analysis and discussion of the scenarios consider how value is created within circular economy and the integral role that the consumer and the IT play within it. The study provides insights on how the FMCG sector might participate in the CE and in doing so provides a basis for further research in this area. Future areas for research are outlined.